Double Prophylaxis for Deep Venous Thrombosis in Patients With Gynecologic Oncology Who Are Undergoing Laparotomy: Does Preoperative Anticoagulation Matter?. Issue 6 (1st August 2011) - Whitworth, Jenny M.; Schneider, Kellie E.; Frederick, Peter J.; Finan, Michael A.; Reed, Eddie; Fauci, Janelle M.; Straughn, J. Michael; Rocconi, Rodney P.
Abstract : Objective: Double prophylaxis for deep venous thrombosis (DVT) with thromboprophylaxis plus sequential compression devices (SCDs) is recommended for high-risk surgical patients with gynecologic oncology. Despite the use of preoperative thromboprophylaxis in clinical trials, the schedule of perioperative low molecular-weight heparin varies widely. We sought to determine the effectiveness and adverse effects of a preoperative dose of anticoagulation in patients with gynecologic oncology. Methods: A multi-institutional chart review from January 2006 to July 2008 was performed. Patients with gynecologic oncology who received double prophylaxis for laparotomy were eligible. The patients were grouped according to whether they received preoperative anticoagulation (YES PREOP vs NO PREOP). All patients received postoperative low molecular-weight heparin for thromboprophylaxis and SCDs until discharge. Demographic, surgicopathologic, and complication data were collected. Results: A total of 239 patients were identified: YES PREOP (n = 101) and NO PREOP (n = 138). Groups were similar with respect to demographics, diagnosis, and length of hospital stay. There were 2 DVTs in the YES PREOP group compared with 11 in the NO PREOP group ( P = 0.04; relative risk, 0.77). There were also fewer DVT-attributable deaths in the YES PREOP group (0 vs 2; P < 0.001). Postoperative hematocrit (30.2% vs 31.4%; P = 0.42) and number of transfusions (26 vs 14; P = 0.31) were similar. Conclusion: The use of preoperative anticoagulation seems to significantly decrease the risk of DVT in this patient population, and complication rates are not increased. Patients receiving double prophylaxis should receive a preoperative dose of anticoagulation for maximum benefit.